Association Between Diet-Related Inflammation and COPD: Findings From NHANES III - Liu, Haiyue; Tan, Xilan; Liu, Zuheng; Ma, Xiaobo; Zheng, Yanqing; Zhu, Bo; Zheng, Gangsen; Hu, Yuehong; Fang, Lili; Hong, Guolin (Frontiers in Nutrition, 2021)
Background&Aims: Little is known about diet-related inflammation in chronic obstructive pulmonary disease (COPD). In this study, we aimed to explore the association between COPD and dietary inflammatory index (DII) scores in adults over 40 years old. Methods: Data were obtained from the 2013-2018 National Health and Nutrition Examination Survey (NHANES). In the present study, 9929 participants were included and analyzed. The DII score was calculated and divided into tertiles. Logistic regression analysis was performed to determine the odds ratios of DII tertiles. Results: Participants were categorized into COPD (565, 5.69%) and non-COPD groups (9364, 94.31%) according to interview information. COPD individuals had higher DII scores than non-COPD individuals (0.429 ± 1.809 vs. -0.191 ± 1.791, p < 0.001). The highest DII score tertile included 46.55% of COPD individuals and was associated with lower family incomes and education and a higher smoking rate (p < 0.01). The odds ratios (95% CIs) of COPD according to logistic regression were 0.709 (0.512-0.982) for T1 and 0.645 (0.475-0.877) for T2 of the DII score (p = 0.011). Conclusion: Higher DII scores were positively correlated with COPD in participants over 40 years old. These results further support that diet can be used as an intervention strategy for COPD management.